STRATEGI AKOMODASI KOMUNIKASI DALAM INTERAKSI ANTAR BUDAYA SUKU MELAYU (TEMPATAN) DAN SUKU JAWA DI DESA BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN PROVINSI RIAU - Septa Alviana; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Interaction between people of different cultures often happens in everyday life. In the interaction between the cultures, there is an understanding that focuses on the role of verbal and nonverbal communication in the conversation, which was based on the belief that people from different cultural communities will adjust to accommodate other cultures. Each occurrence of communication accommodation, there are strategies used to stabilize the communication process they were doing, such a strategy is the convergence and divergence and overaccomodation label. This study aims to determine the forms of strategy in the accommodation as a strategy of convergence, divergence and overaccomodation labeling to the speaker by the people of the Malays and Javanese in the village of Bukit Gajah District of Ukui Pelalawan.This study used a qualitative descriptive approach of symbolic interaction and using data collection techniques of observation, interviews, and dokumentation. Informants in this study amounted to 20 were determined by purposive samplingThe results showed that the shape of the convergence strategy undertaken by the community of the Malays and Javanese in the village of Bukit Gajah are using the language of his interlocutor, physical approach, adjust the speed and volume, adjusting ornaments used, as well as customize the dress code when communicating. Shape divergence strategy using different languages with the language of his interlocutor, does not create body movement which describes interests, trying to distinguish the volume and rate of speech, trying to create distance limitations, and show differences ranging from social status to ethnic differences when communicating. Causes overaccomodation labeling is due to an error in using the language of his interlocutor, excessive share the experience and knowledge the speaker, as well as excessive in adapting the communication distance. The goal are diverse ranging from can easily familiarize themselves, demonstrate the existence, providing motivation to interlocutor, but its main purpose is to create a balanced communication between ethnic Malay and JavaneseKeywords: intercultural communication, Accommodation Communication, Convergence, Divergence, Overaccomodation